Population’s Perception of a Dispute over Territorial Boundaries between the Mexican States of Campeche and Quintana Roo (2020)
A territorial dispute and a lack of a consistent inter-municipal management model between Campeche and Quintana Roo, Mexico, is causing inefficiency in and untimely responses to the sustainable development of this rural tourist area, which in turn gives rise to “absence of the state” or “disorderly intervention.” This article aims to determine the population’s perception of the territorial dispute and its impacts and diagnose its living conditions. It results from the review of bibliographic, institutional, and newspaper sources, but, above all, the fieldwork carried out through surveys and non-participant observation using a photographic camera. Therefore, an approach is made to those suffering the consequences of the territorial conflict and their view.